Penguatan Kesadaran Hukum Warga Muda terhadap Tindak Pidana Kekerasan Seksual Berbasis Elektronik Berdasarkan UU TPKS: (Studi Pengabdian Masyarakat di Desa Molowahu, Kecamatan Tibawa) - Imran, Suwitno Yutye; Lisnawaty W. Badu; Nurvazria Achir; Yahya, Agung Prayuda; Janwar Hippy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid advancement of information technology has triggered an escalation in Electronic-Based Sexual Violence (KSBE), threatening the safety of young people in cyberspace. The community service activity serving as the focus of this study was conducted in Molowahu Village, Tibawa District, Gorontalo Regency, where such vulnerability was exacerbated by low legal awareness and the limitations of pre-existing regulations—prior to the enactment of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS)—which often led to the secondary victimization (or